Pendampingan Pengelolaan Umkm Berbasis Syariah untuk Meningkatkan Kemandirian Finansial : Studi Kasus Kedai Serly - Dela Puspita Sari; Elia Sulastri; Lika Susanti; Yetti Afrida; Idwal B (PT Pustaka Cendekia Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic growth, yet many business owners still struggle with managing their finances according to Sharia principles. This study aims to implement Sharia-based mentoring for Kedai Serly, a culinary MSME in Bengkulu City, to improve financial independence through halal and sustainable financial management. The method used is Participatory Action Research (PAR), emphasizing active collaboration between researchers and business owners in problem identification, solution planning, training, practical implementation, and evaluation. Results show a significant increase in the business owner's understanding of Sharia financial concepts, rising from 43% to 85% based on questionnaire assessments. The business partner began applying more orderly financial recording, separating personal and business funds, and avoiding transactions involving riba (interest). Additionally, there was increased awareness of running a business in line with Islamic values and interest in accessing Islamic microfinance. In conclusion, participatory Sharia-based mentoring effectively fosters healthy and financially independent business practices, and it is worth replicating in other MSMEs to support a more inclusive Islamic economic ecosystem.